1993
DOI: 10.1128/jvi.67.3.1688-1692.1993
|View full text |Cite
|
Sign up to set email alerts
|

The E3L and K3L vaccinia virus gene products stimulate translation through inhibition of the double-stranded RNA-dependent protein kinase by different mechanisms

Abstract: Vaccinia virus has evolved multiple mechanisms to counteract the interferon-induced antiviral host cell response. Recently, two vaccinia virus gene products were shown to interfere with the activity of the double-stranded RNA-dependent protein kinase (PKR): the K3L gene product and the E3L gene product. We have evaluated the efficiency by which these gene products inhibit PKR and whether they act in a synergistic manner. The effects of the two vaccinia virus gene products were compared in an in vivo system in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(103 citation statements)
references
References 16 publications
(13 reference statements)
2
96
0
1
Order By: Relevance
“…Third, M2L is probably involved in the regulation of host NF-kB responses in virus infection which may potentially influence inflammation and the severity of vaccinia infection [40]. Fourth, K3L gene is an immunomodulatory and anti-apoptotic gene that inhibits IFN intracellular signaling pathway by preventing RNA-dependent protein kinase (PKR) activation [41][42][43]. Thus, deletion of K3L in vaccinia virus may render the virus sensitive to the antiviral effects of IFN and probably limit disease progression in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Third, M2L is probably involved in the regulation of host NF-kB responses in virus infection which may potentially influence inflammation and the severity of vaccinia infection [40]. Fourth, K3L gene is an immunomodulatory and anti-apoptotic gene that inhibits IFN intracellular signaling pathway by preventing RNA-dependent protein kinase (PKR) activation [41][42][43]. Thus, deletion of K3L in vaccinia virus may render the virus sensitive to the antiviral effects of IFN and probably limit disease progression in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to counteract the effects of host IFN response and PKR activation, viruses have developed multiple mechanisms to suppress PKR activation [71]. Several lines of evidence support the fact that viral genes (vaccinia virus, adenovirus and hepatitis C virus) encode proteins that inhibit the IFN pathway by targeting PKR [72,73]. For instance, non-structural 5A protein of hepatitis C virus (HCV) causes repression of PKR activation, eventually leading to suppression of host IFN response.…”
Section: Mapk Pathwaymentioning
confidence: 99%
“…Many viruses synthesize dsRNA-binding proteins that prevent activation of PKR by interacting with and sequestering any free dsRNA molecules. 228,229 The first such dsRNA-binding protein identified in this regard was reovirus sigma 3. 230 The reovirus sigma 3 protein does not have catalytic activity and it was shown that inhibition of PKR by this protein could be overcome by the addition of excess dsRNA, 229 suggesting that the protein acts as a competitive inhibitor by directly binding to dsRNA.…”
Section: Sequestration Of Dsrnamentioning
confidence: 99%